METHODS OF THE RADAR SITUATION COMPUTER MODELLING - Прокопенко, І.; Мігель, С. (Science-based technologies, 2012)
The modeling methods of radar signal and clutter which are received as a result of sounding of the environment by the pulse radar are described. These methods are used in the simulation computer program to provide statistical estimation of the radar target detection efficiency and for the efficient solving of signal, processing tasks.